Utilización del láser en experiencias por difracción : cálculo de la longitud de onda de una radiación luminosa - Garrigós Oltra, Lluís (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This paper is an attempt to underline the importance of the use of didactic laser systems to carry out qualitative and, aboye all, quantitative experiencies concerning the properties of the luminous waves, at a secondary school level. Such experiences direct the interest of (he student towards a series of concepts which so far have been characterizad by a lack of experimental resources at that level.